Spatial connectedness imposes local‐ and metapopulation‐level selection on life history through feedbacks on demography. (19th November 2019) - Masier, Stefano; Bonte, Dries
Abstract: Dispersal evolution impacts the fluxes of individuals and hence, connectivity in metapopulations. Connectivity is therefore decoupled from the structural connectedness of the patches within the spatial network. Because of demographic feedbacks, local selection also drives the evolution of other life history traits. We investigated how different levels of connectedness affect trait evolution in experimental metapopulations of the two‐spotted spider mite. We separated local‐ and metapopulation‐level selection and linked trait divergence to population dynamics. With lower connectedness, an increased starvation resistance and delayed dispersal evolved. Reproductive performance evolved locally by transgenerational plasticity or epigenetic processes. Costs of dispersal, but also changes in local densities and temporal fluctuations herein are found to be putative drivers. In addition to dispersal, demographic traits are able to evolve in response to metapopulation connectedness at both the local and metapopulation level by genetic and/or non‐genetic inheritance. These trait changes impact the persistence of spatially structured populations.